2016
DOI: 10.1007/s11096-016-0334-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an alternative extended-infusion piperacillin–tazobactam dosing strategy for the treatment of gram-negative infections

Abstract: Introduction To enhance the probability of pharmacodynamic target attainment, piperacillin-tazobactam can be administered as either a continuous or extended-infusion dosage regimen for the treatment of gram-negative infections. Four hour extended-infusions of piperacillin-tazobactam 3.375 g administered intravenously (IV) every 8 h have been widely studied as an alternative to conventional, intermittent dosage regimens with largely favorable outcomes. Objective To assess the clinical and economic impact of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Compared to the conventional intermittent dosage regimen, prolonged piperacillin/tazobactam infusion resulted in shorter ICU and hospital LOS among adult critically ill patients (ie, saving 0.6 days and 5.6 days, respectively), 29 a significantly lower rate of readmission within 30 days of hospital discharge (1.2% vs 13.7%, P =0.002), 30 and greater PTA in critically ill patients receiving continuous renal replacement therapy or critically ill patients with severe sepsis or septic shock undergoing continuous venovenous hemofiltration. 31 , 32 …”
Section: Resultsmentioning
confidence: 97%
“…Compared to the conventional intermittent dosage regimen, prolonged piperacillin/tazobactam infusion resulted in shorter ICU and hospital LOS among adult critically ill patients (ie, saving 0.6 days and 5.6 days, respectively), 29 a significantly lower rate of readmission within 30 days of hospital discharge (1.2% vs 13.7%, P =0.002), 30 and greater PTA in critically ill patients receiving continuous renal replacement therapy or critically ill patients with severe sepsis or septic shock undergoing continuous venovenous hemofiltration. 31 , 32 …”
Section: Resultsmentioning
confidence: 97%
“…An additional two studies that met the inclusion criteria were acknowledged through checking references of relevant studies. Twenty-three studies met the described inclusion criteria and were included in the systematic review (13,14,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)15,33,34,(16)(17)(18)(19)(20)(21)(22). The article selection process is illustrated in Figure.1 and selected studies comparing clinical outcome between CI and II of piperacillin are listed in Table.2.…”
Section: Search Resultsmentioning
confidence: 99%
“…Fifteen of the included studies reported length of hospital stay (13,14,31,33,34,36,38,15,16,18,23,24,26,29,30). Pooling of studies showed that patients receiving C/PI had a signi cantly shorter length of hospital stay (2101 patients; Mean Difference -1.27, 95% C.I -2.45-0.08, P = 0.04; Figure 9) The meta-analysis suggests there is a signi cant reduction in the length of hospital stay in patients receiving C/PI compared to those receiving II.…”
Section: Length Of Hospital Staymentioning
confidence: 99%
“…Eighteen of the included studies reported patient mortality rates (Table 1) (13,14,(28)(29)(30)(31)(32)(33)(34)36,(15)(16)(17)(18)20,21,24,27). Statistically significantly fewer mortality rates were found among patients receiving C/PI compared with patients receiving conventional II (3100 patients; OR 0.68, 95% C.I 0.55-0.84, P = 0 .0003; Fig.…”
Section: Mortalitymentioning
confidence: 99%
“…Fifteen of the included studies reported length of hospital stay (13,14,31,(33)(34)(35)37,15,16,18,23,24,26,29,30). Pooling of studies showed that patients receiving C/PI had a significantly shorter length of hospital stay (2101 patients; OR -1.27, 95% C.I -2.45-0.08, P = 0.04; Fig.…”
Section: Length Of Hospital Staymentioning
confidence: 99%